Zinc as Allosteric Ion Channel Modulator: Ionotropic Receptors as Metalloproteins - Garcia Huidobro-Toro, J; Peralta-Peralta, F (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
Zinc is an essential metal to life. This transition metal is a structural component of many proteins and is actively involved in the catalytic activity of cell enzymes. In either case, these zinc-containing proteins are metalloproteins. However, the amino acid residues that serve as ligands for metal coordination are not necessarily the same in structural proteins compared to enzymes. While crystals of structural proteins that bind zinc reveal a higher preference for cysteine sulfhydryls rather than histidine imidazole rings, catalytic enzymes reveal the opposite, i.e., a greater preference for the histidines over cysteines for catalysis, plus the influence of carboxylic acids. Based on this paradigm, we reviewed the putative ligands of zinc in ionotropic receptors, where zinc has been described as an allosteric modulator of channel receptors. Although these receptors do not strictly qualify as metalloproteins since they do not normally bind zinc in structural domains, they do transitorily bind zinc at allosteric sites, modifying transiently the receptor channel’s ion permeability. The present contribution summarizes current information showing that zinc allosteric modulation of receptor channels occurs by the preferential metal coordination to imidazole rings as well as to the sulfhydryl groups of cysteine in addition to the carboxyl group of acid residues, as with enzymes and catalysis. It is remarkable that most channels, either voltage-sensitive or transmitter-gated receptor channels, are susceptible to zinc modulation either as positive or negative regulators. © 2016 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: zinc coordination; protein zinc ligands; zinc and ionotropic receptors; zinc allosteric modulator; zinc-activated channel; zinc coordination sphere